Plasticity of root growth and respiratory activity Root responses to above-ground senescence, fruit removal or partial root pruning in soybean - Fanello, Diego Darío (Plant science : an international journal of experimental plant biology, 2020)
Copyright © 2019 Elsevier B.V. All rights reserved.